2007
DOI: 10.1111/j.1442-2042.2007.01847.x
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic pattern in adults with nocturnal polyuria: The possible contribution of blood pressure to the worsening of nocturnal polyuria

Abstract: Aim: The present study was undertaken to investigate diuresis rate determinants of nocturnal polyuria (NP) in adults. Subjects and Methods: A total of 33 patients aged 50-87 years (mean: 68.6), with nocturnal urine volumes exceeding 10 mL per kg body weight based on records of a frequency-volume chart, were enrolled to evaluate the relationships between diuresis rates and related variables. Multiple regression analyses were conducted to identify diuresis rate determinants, including brain natriuretic peptide. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…In the present study, sleep architectures were not measured; moreover, causality of the association between nocturia and ABP cannot be ascertained because the present study was cross‐sectional. Also, a possible contribution of high blood pressure on nocturia has been reported, and natriuretic peptide may mediate it . Further research is needed to better understand whether improvement of nocturia decreases nighttime BP and increases dipping.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, sleep architectures were not measured; moreover, causality of the association between nocturia and ABP cannot be ascertained because the present study was cross‐sectional. Also, a possible contribution of high blood pressure on nocturia has been reported, and natriuretic peptide may mediate it . Further research is needed to better understand whether improvement of nocturia decreases nighttime BP and increases dipping.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding age, nocturia caused by nocturnal polyuria is generally a common complaint in the elderly, because day to night ratios of urinary excretion gradually reduce with age, which may be implicated in cardiac function, hormonal changes such as arginine vasopressin secretion and so on. [17][18][19] Hypertension, which is common in elderly patients, is also related to increasing nocturnal diuresis. 18,19 Meanwhile, in periods of dialysis before RTX, autonomic dysfunction, which patients with uremia receiving dialysis commonly have, 20 may be implicated in nocturnal polyuria.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Hypertension, which is common in elderly patients, is also related to increasing nocturnal diuresis. 18,19 Meanwhile, in periods of dialysis before RTX, autonomic dysfunction, which patients with uremia receiving dialysis commonly have, 20 may be implicated in nocturnal polyuria. Thus, age and periods of dialysis before RTX could affect nocturnal polyuria after RTX.…”
Section: Discussionmentioning
confidence: 99%
“…A hypertonic saline infusion test, one of the practical evaluation methods of hypothalamo-hypophyseal function, was conducted to examine the plasma AVP release responsiveness of the hypothalamoposterior pituitary system to osmolality changes of increased plasma sodium in patients with NP. 13,24,25 For this test, a 5% hypertonic saline infusion was given at a rate of 0.05 mL/kg per min for 120 min on 31 patients in the NP group and eight patients in the non-NP group. All of the patients were in a recumbent position while the test was being conducted.…”
Section: Comparison Of Osmotic Response Of Plasma Avp Following 5% Hymentioning
confidence: 99%
“…Recently there have been reports indicating that the link between nocturia and cardiovascular disorders has clinical implications 8–10 . Our previous studies indicated the importance of blood pressure on increased nocturnal urine production in nocturic older adults with NP, 11–13 and it has also been well documented that hemodynamic changes that occur with aging likely accompany disturbed patterns of diuresis and urinary solutes excretion profiles 14–17 . Thus, etiological factors for nocturia or NP may arise from similar grounds involved in the hemodynamic changes associated with aging.…”
Section: Introductionmentioning
confidence: 98%